Aspects of antiquity - Finley, M. I. (Penguin books, 1960)
In this collection of 15 essays the author of "The Ancient Greeks" and "The World of Odysseus" highlights aspects of the ancient world ranging from Minoan Crete to the decline of the Roman Empire 20 centuries later. He describes archaeological discoveries which have made the lost civilization of Crete more accessible, he argues that the Greeks may never have taken Troy, and discusses the trial of Socrates in 399 BC. This book combines up-to-date scholarship with an historical imagination to help the reader to continue a dialogue between the past and the present.